TEACHER COMPETENCY IMPROVEMENT MANAGEMENT MODEL THROUGH HYBRID TRAINING IN THE IMPLEMENTATION OF DEEP LEARNING IN NUMFOR PAPUA - Beni Ramadhan; Albert Efendi Pohan; Jaya Dwi Putra (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The progressiveness of the quality of education in formal educational institutions is implemented through a number of strategies, namely strengthening the readiness of new students, improving teacher competence, updating the curriculum, improving the quality of learning and evaluation of learning outcomes, providing adequate teaching materials, and providing adequate learning facilities. The data analysis techniques implemented involve quantitative and qualitative approaches. Quantitative analysis was carried out by comparing the results of the pretest and posttest using descriptive statistics to measure the progressiveness of the population of competencies of 13 teachers of SMPN 3 Numfor Barat and 13 teachers of SMKN 3 Kemaritiman Biak after training. Partner teachers in Numfor Papua face a number of significant challenges in improving the quality of learning. One of the main problems is the low understanding of the innovative deep learning approach, focusing on comprehensive student involvement in the learning process in order to develop critical, creative, and collaborative thinking skills. research findings indicate that a number of 20 teachers at SMPN 3 and SMKN Kemaritiman Numfor Papua experienced progressive abilities in designing and implementing deep learning strategies that focus on critical, creative, and joyful learning thinking and the implementation of deep learning, especially joyful learning, teachers are able to create a dynamic and meaningful learning atmosphere for students.